BRIP1 rs10744996C>A variant increases the risk of chronic obstructive pulmonary disease in the Mongolian population of northern China. Issue 11 (24th September 2020) - Wang, Jing; Sun, Dejun; Lu, Wenju; Zhang, Zili; Zhang, Chenting; Hu, Ke
Abstract : New Findings: What is the central question of this study? What is the role of breast cancer type 1 interacting protein C‐terminal helicase 1 ( BRIP1 ) polymorphism in chronic obstructive pulmonary disease (COPD)? What is the main finding and its importance? Variant rs10744996C>A of BRIP1 increases the susceptibility of the Mongolian population to COPD. The expression of BRIP1 was significantly reduced in cigarette smoke extract‐treated airway epithelial cells. Abstract: Cigarette smoke is a major environmental pollutant that can induce DNA damage in humans. The development and progression of chronic obstructive pulmonary disease (COPD) are known to be related to the impairment of DNA repair. Breast cancer type 1 interacting protein C‐terminal helicase 1 (BRIP1) plays an important role in DNA interstrand crosslink repair and double‐strand break repair. However, the role of BRIP1 polymorphisms in COPD has not been previously described. In this study, whole genome sequencing was used to identify mutations, and single nucleotide polymorphism (SNP) genotyping was used to verify the selected SNPs. In addition the BRIP1 expression levels in 16HBE and A549 airway epithelial cells treated with or without cigarette smoke extract (CSE) were measured using western blotting and RT‐qPCR. Rs10744996C>A in the 3′‐untranslated region (3′UTR) of BRIP1 was then genotyped in 1296 COPD cases and 988 healthy control subjects from a Mongolian population in northern China. Significant differences in the distribution of rs10744996C>A variants between COPD and control groups ( P  = 0.001) were identified. Rs10744996C>A was found to be associated with significantly increased COPD risk (adjusted odds ratio = 1.60, 95% CI = 1.30–1.98, P  < 0.0001). Additionally, rs10744996A genotype was found to interact with a family history of cancer and a history of x‐ray exposure ( P  = 0.028 and 0.009, respectively). BRIP1 expression levels in 16HBE and A549 cells treated with CSE were significantly lower compared to the control treated cells. The rs10744996C>A variant of BRIP1 increased the COPD susceptibility of the Mongolian population cohort. BRIP1 mRNA and protein expression levels were significantly reduced in conjunction with CSE‐induced DNA damage in 16HBE and A549 cells. Abstract :